Gambaran Kondisi Ventilasi dan Kelembaban Udara Kamar Tidur Penderita ISPA - Azhar Hisbullah; Burhan Muslim; Erdi Nur; Wijayantono Wijayantono; Darwel Darwel (Jurnal Kesehatan Lingkungan Mandiri, 2026)
Acute Respiratory Infection (ARI) remains a highly prevalent communicable disease. In Koto Tangah Village, Tanah Datar Regency, 42 ARI cases were reported during the last three months based on data from Tanjung Emas Health Center in 2025. Environmental factors, particularly bedroom ventilation and air humidity, are suspected to contribute to ARI incidence. This study aimed to describe the ventilation and air humidity conditions of bedrooms occupied by ARI patients. A descriptive quantitative design was used with total sampling of 42 houses of ARI patients. Primary data were collected through direct measurements using a measuring tape and humidity meter, while secondary data were obtained from Tanjung Emas Health Center. Data were analyzed using univariate analysis. The results showed that 69.0% of bedrooms had inadequate ventilation (≤10% of floor area), and 81.0% had air humidity outside the recommended range of 40–60%. In conclusion, most bedrooms of ARI patients did not meet health standards, indicating the need to improve air circulation and maintain appropriate indoor humidity to reduce the risk of ARI.